2017
DOI: 10.2174/1574892812666170619125503
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibitors of NAD Biosynthesis as Potential An ticancer Agents

Abstract: The main objective of this article is to review the recent patents which develop and implicate the chemical inhibitors of the key NAD+ biosynthetic enzymes for cancer treatment. We first discuss the biological principles of NAD+ metabolism in normal and malignant cells, with a focus on the feasibility of selectively targeting cancer cells by pharmacological inhibition of nicotinamide phosphoribosyltransferase (NAMPT) and indoleamine/tryptophan 2,3-dioxygenases (IDO/TDO), the rate-limiting salvage and de novo N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…NAMPT inhibition also leads to the attenuation of glycolysis, which results in further perturbation of carbohydrate metabolism in cancer cells (11). Therefore, NAMPT has been proposed as a promising anticancer target (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…NAMPT inhibition also leads to the attenuation of glycolysis, which results in further perturbation of carbohydrate metabolism in cancer cells (11). Therefore, NAMPT has been proposed as a promising anticancer target (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…NAMPT is overexpressed in many different types of tumors, and its expression appears to be associated with cancer progression [22,88]. Thus, many cancer biologists have explored the strategy of inhibiting NAMPT expression as a means of reducing tumor growth [88][89][90]. Although preclinical studies have shown this approach to be very beneficial for reducing various tumor types, this anticancer benefit is associated, unfortunately, with severe retinal toxicity.…”
Section: Nad + and Aging Retinamentioning
confidence: 99%
“…Therefore, NAMPT inhibitors including FK866 were originally developed as anti-cancer drugs. [23][24][25] Yet, it has been shown that NAMPT inhibitors also exert potent anti-inflammatory effects in the peripheral system. 26,27 We and others have shown that NAMPT inhibitors have neuroprotective effects, mainly through their anti-neuroinflammation effects.…”
Section: Introductionmentioning
confidence: 99%